Kształtowanie kapitału społecznego w szkole – wprowadzenie do problemu - Potulicka, Eugenia (Wydawnictwo Naukowe UAM, 2012)
The article deals with shaping human capital in school. Trust is the key element of this capital and the other one is enhancing community ties. Unfortunately, we live with the culture of distrust in Poland. Common core values are necessary condition for building trust among peo-ple and students as well. The biggest problem is with the activities of our ministry of education and teacher’s distrust in the proposed reforms in schools.
Forming social capital at school: introduction
Keywords: human capital; trust; distrust; school